Effects of Acetone Fraction From Buchenavia tomentosa Aqueous Extract and Gallic Acid on Candida albicans Biofilms and Virulence Factors - Teodoro, Guilherme R.; Gontijo, Aline V. L.; Salvador, Marcos J.; Tanaka, Márcia H.; Brighenti, Fernanda L.; Delbem, Alberto C. B.; Delbem, Ádina C. B.; Koga-Ito, Cristiane Y. (Frontiers in Microbiology, 2018)
A promising anti-Candida activity of Buchenavia tomentosa extracts was recently described. In the present work, experiments were carried out to determine the fraction with higher antifungal activity from a Buchenavia tomentosa extract. Acetone fraction (AF) was obtained from the aqueous extract from dried leaves (5 min/100˚ C) and it was the most effective one. Gallic acid (GA) was identified by electrospray ionisation mass spectrometry (ESI-MS) and also chosen to perform antifungal tests due to its promising activity on C. albicans. Minimal inhibitory and fungicidal concentrations (MIC and MFC) were determined by broth microdilution technique. The effect on virulence factors of C. albicans was evaluated, and the cytotoxicity was determined. MIC50 and MIC90 values were both equal to 0.625 mg.ml-1 for AF and 2.5 and 5 mg.ml-1, respectively, for GA. AF and GA showed ability to inhibit C. albicans adherence and to disrupt 48h-biofilm. AF and GA were effective in reducing the formation of hyphae of C. albicans SC5314. AF and GA decreased adherence of C. albicans to oral epithelial cells. AF and GA showed slight to moderate toxicity to Vero cells. This result suggests further studies for topic use of these compounds. AF, which contains a combination of several molecules, presented greater potential of antimicrobial activity than GA, with lower values of MIC and lower cytoxicity.